Female role models in school religious education and their perception by female students in the final years of secondary school - Maciejewska, Magdalena (British Journal of religious education, 2024)
The present article discusses female students’ perception of the female role models introduced to them during religious education classes in Poland. Besides imparting knowledge, the teaching of religious classes in schools, a part of religious education, aims at shaping attitudes. Therefore, presenting young people with role models who can inspire them and be a reference point concerning their behaviour should be a vital component of religious education. The current research shows, however, that this is a neglected area. This article is based on a research study comprising focus group interviews. The participants were adult students in the final grades of secondary school who had completed the entire cycle of religious education at school. The article is structured as follows. The first section discusses the relationship between the role models presented to students during religious education classes and the shaping of their identity vis-a-vis the morphogenetic approach of M. Archer. The second section focuses on the female personal role models mentioned in the core curriculum and religious education textbooks. This is followed by a delineation of the methodological assumptions of the present research and a discussion of the results.